THROUGH PRACTICE LENS: How do the organizing of Artistic and Cultural Projects can induce School Management - de Rezende, Bruno Ricardo Peixoto (Extensão em Foco, 2018)
The objective of this essay is to propose the study of School Management from the look on the practices in the organization of Artistic and Cultural Projects. To do this, we use the Practice Lens approach, which aims to establish a relationship between human activity and macrossocial phenomena. In this approach, management is treated as a continuous process, a constant organizing based on the characteristics of the school. The result of 2 years of observation and based on the lack of studies focused on daily management, this study focuses on the relevance of the School's specificity in the elaboration of ideas for the study of its management, presenting the practices of social project management in schools as an alternative for the development of school management based on it’s specificity.